Evaluation of Construction Industry payment and Adjudication Act 2012 (CIPPA): An Overview Perspective by Contractors in Kuala Lumpur - Yap, Mun Hoe (2015)
Construction Industry Payment and Adjudication Act 2012 (CIPAA) has come into operation in April 2014 to facilitate the cash-flow problem in construction industry. There were comments from the industry discussing the benefits and drawbacks of CJPAA. This study is then proposed to examine if CIPAA develops a successful mechanism to solve payment problem in Malaysian construction industry. Since contractors were expected main users, convenient-sampling interviews were then conducted with contractors in Kuala Lumpur. From the interviews, most senior construction practitioners, including some who are having more than thirty-year (30) experience, did not have detail knowledge on CIPAA. This shows the insufficient promotion of CIPAA in the construction industry. Most contractors agreed that CIPAA is beneficial to Malaysian contractors and mast of them would initiate statutory adjudication when payment disputes. However, most of them hold that this adjudication proceeding is not efficient enough to solve the payment dispute. Other than drawbacks and benefits, this study also lists the possible challenges to CIPAA that pointed by the industry and suggests possible improvement for the future development of CIPAA.